Kajian Studi Trotoar Di Pasar Batang (Pintu Sebalah Barat Pasar) - Wahyudiono; Meidi Sapta Anggara; Andry Wisnu Pabowo (Fakultas Teknik dan Rekayasa, 2024)
Sidewalks are road supporting facilities in Law no. 22 of 2009 concerning road traffic and transportation, hereinafter referred to as the Road Traffic and Transportation Law, the availability of sidewalks must provide safety and comfort to pedestrians passing by. The subject of pedestrians itself is not only intended for normal people. But also to all levels of society, including people with disabilities, such as the blind, wheelchair users and others. The discussion that will be studied in this paper is related to legal protection for people with disabilities who pass on sidewalks in light of the traffic and road transportation laws. The purpose of this writing is to analyze whether the traffic and road transportation laws provide legal protection to people with disabilities who pass on the sidewalk because the sidewalk is one of the supporting facilities mentioned. The type of research used in this research is descriptive. The results obtained from this research are that the traffic and road transportation law has provided legal protection through Article 121 which states that pedestrians have the right to the availability of sidewalks and other facilities on the highway. This explains that pedestrians have full rights to cross the road without interference from anywhere.